Administering intramuscular injections: How does research translate into practice over time in the mental health setting? - Wynaden, Dianne; Tohotoa, Jenny; Al Omari, Omar; Happell, B.; Heslop, Karen; Barr, L.; Sourinathan, V. (Churchill Livingstone, 2015)
Background: Increasingly, mental health nurses are expected to base their clinical practice on evidence based knowledge and many of the practice traditions that have passed between generations of nurses must now be examined within this scientific context. Since 2000, there has been an increasing debate on what is best practice for the administration of intramuscular injections particularly in relation to site selection, needle size and technique. Weight gain associated with second generation long acting antipsychotics influences the site and needle size for effective medication delivery. Aim: To determine intramuscular injecting practice choices made by nurses working in the mental health setting in 2006 compared to those made by a similar group of nurses in 2012. Methods: A descriptive cross sectional study conducted across two time points: 2006 (93 participants) and 2012 (245 participants) utilising the same questionnaire designed to measure nurses' intramuscular injecting practice choices. Results: Data were analysed using SPSS version 20 package. Six statistically significant practice changes were recorded related to needle size, site selection and the use of the Z-tracking technique. A continued higher usage of the dorsogluteal site was also reported in 2012 contrary to the recommendations in the current research for the ventrogluteal site. Conclusion: Whilst some practice changes occurred, translation of research into evidenced based practice is challenging and definitive best practice in the administration of intramuscular injections remains unclear. Education and randomised controlled trials are needed to provide the evidence to ensure the delivery of safe and effective intramuscular injecting practice.